Why a Son Needs a Mom - Lang, Gregory E.; Hill, Susannah Leonard, 1960-; Yerrill, Gail (Naperville, Illinois : Sourcebooks Wonderland, 2021)
In this rhyming adaptation for children of "Why a Son Needs a Mom: 100 Reasons" by Gregory E. Lang, a mother holds her newborn son and lists all the ways she will help him grow, reminding him to be curious, courageous, playful, and, most important, true to himself.
Ages 4-8.
Grades 2-3.
Keywords: Stories in rhyme -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Animals -- Juvenile fiction